IRETA research news - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
J.R. Finlay, of the Atoll Research and Development Unit at the University of the South Pacific, reports that split applications of nitrogenous fertilizers give higher yield increases than single applications. Finlay's work m Kiribati also indicates...